Key Features of Personalized Learning - Çullhaj, Salian (European Journal of Multidisciplinary Studies, 2017)
The term personalized learning, or personalization, refers to a diverse variety of educational programs, learning experiences, instructional approaches, and academic-support strategies that are intended to address the distinct learning needs, interests, aspirations, or cultural backgrounds of individual students.
Keywords: Key Features of Personalized Learning